Inclusive arts education in two Scandinavian primary schools: a phenomenological case study. Issue 5 (4th May 2017) - Ferm Almqvist, Cecilia; Christophersen, Catharina
ABSTRACT: Previous studies indicate that ideas related to special education could influence the way arts education is performed and motivated in schools. Further investigation is therefore required in order to raise awareness of how perspectives on inclusion can serve as a starting point for arts education, and vice versa. This article takes it starting point in an ethnographic double case study of arts education practices. Data were collected during the school year 2013/2014 in two Scandinavian schools (for pupils aged 6–13) with an articulated commitment to the arts. The methods used for data collection were observation and interviews. The material was analysed from a phenomenological point of view, and the analysis showed a predominantly holistic view of inclusion in the two schools. Five dimensions of inclusion were identified through the analysis: providing arts education for all, being connected to something larger, allowing access to different forms of expression and communication, establishing preconditions for holistic inclusion, and developing special arts education . The results indicate that these schools have made considerable progress in developing an inclusive arts learning environment. Results also suggest that a holistic inclusive view of education encourages a functional and vivid arts education for 'all', both inside and outside the classroom.